PENINGKATAN KAPASITAS DIGITALISASI PEMBELAJARAN DAN KEHUMASAN DI MI CAWAN MELALUI PENYEDIAAN PERANGKAT KONTEN DIGITAL - Haryono Setiadi; Dewi Wisnu Wardhani; Rini Angrainingsih; Afrizal Doewoes; Hasan Dwi Cahyono (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2025)
Madrasah Ibtidaiyah (MI) Cawan faces challenges in adopting digital technology, reflected in its conventional learning processes and manual public relations. The scarcity of devices and limited teacher skills have led to low student engagement and restricted school promotion outreach. This community service program aimed to enhance the capacity for digitalizing learning and public relations at MI Cawan by providing supporting equipment and improving human resource competencies. A participatory method was implemented in three stages: needs assessment, implementation (a device grant and an intensive workshop), and mentoring and evaluation. The intervention included the provision of a digital content production kit (a mobile device, tripod, microphone, and lighting) and a two-day intensive workshop on basic videography, graphic design using Canva, and video editing with CapCut/VN. The program yielded positive outcomes: the availability of ready-to-use equipment, 85% of teachers becoming capable of creating simple learning videos, and the public relations team publishing five new types of promotional content. Activity on the school's Instagram account increased, with a 40% rise in interaction during the mentoring period. In conclusion, the program successfully accelerated the digital transformation at MI Cawan, promoting the modernization of learning and strengthening the school's public relations strategy.